إمكانية التوليف بين بقايا الجلود والسحابات لتنفيذ مكملات ملبسية منفصلة (الحلي) - الوراقي، سالي فوزي; هيكل، رانيا حسني يوسف Heikal, Rania Husni Yousuf (جامعة المنيا - كلية التربية النوعية, 2018)
يهدف البحث إلى: 1. الاستفادة من بقايا الجلود والسحابات في عمل حلي ملبسية. 2. تنمية التفكير الابتكاري من خلال تصميم حلي ملبسية مبتكرة. 3. استنباط أساليب فنية وتقنية في مجال التوليف لعمل الحلي الملبسية. 4. الحصول على منتج متميز من الحلي قادر على المنافسة ويصلح لعمل مشروعات صغيرة للشباب. وذلك بالاستفادة من بقايا الجلود والسحابات والتوليف بينهما لتنفيذ مكملات ملبسية مبتكرة وتم تنفيذ 25 تصميم من الحلي وتم عمل عدد (2) استمارة استبيان لتقييم التصميمات المنفذة وعرضهم على 15 محكم من المتخصصين و35 من المستهلكات لتقييم التصميمات وكانت النتائج كالآتي: يوجد فروق ذات دلالة إحصائية عند مستوى دلالة (...1) بين استجابات السادة المتخصصين على التصميمات حيث بلغت قيمة (ف) 3.94 ومستوى الدلالة أقل من مستوى المعنوية (...1)، مما يدل على وجود فروق بين التصميمات في الاستبيان ككل. وجود فروق ذات دلالة إحصائية عند مستوى دلالة (...1) بين استجابات السادة المستهلكات على التصميمات المنفذة للمكملات الملبسية المنفصلة (الحلي) من التوليف بين بقايا الجلود والسوست حيث بلغت قيمة (ف) 6.565 ومستوى الدلالة أقل من مستوى المعنوية (...1)، مما يدل على وجود فروق بين التصميمات في هذا المحور. مما يؤكد تحقق الفرض السادس.
The research aims to: 1. Use of leather remnants and zippers in manufacturing clothing supplements. 2. Develop innovative thinking by designing innovative clothing supplements. 3. Developing technical and technical methods in the field of synthesis to manufacture clothing supplements. 4. Obtain premium clothing supplements that are competitive and fit to be the start of small projects based on them. That was by using the remnants of leather and zippers and overlapping between them to create innovative clothing supplements. Twenty-five designs were implemented and (2) questionnaire forms were used to evaluate the designs executed and presented them to 15 arbitrators and 35 consumers to evaluate the designs. The results were as follows: There were statistically significant differences at the level of (...1) among the responses of the specialists in the designs, where the value of (P) 3.94 and the level of significance less than the level of significance (...1), indicating the existence of differences Among the designs in the questionnaire as a whole. There were statistically significant differences at the level of (...1) between the responses of the consumers on the designs of the finished dressings (accessories) of the synthesis between the leather and zipper residues, where the value of (P) 6,565 and the significance level is less than the moral level (...1), Indicating that there are differences between the designs in this axis. Which confirms the achievement of the sixth hypothesis.
Keywords: الجلود -- السحابات -- تصميم الأزياء -- مكملات الملابس -- الحلي الملبسية